Structural behaviors of ultra-high performance engineered cementitious composites (UHP-ECC) beams subjected to bending-experimental study - Ding, Yao; Yu, Ke-Quan; Yu, Jiang-tao; Xu, Shi-lang (Construction & building materials, 2018)
•An ultra-high performance engineered cementitious composites was developed.•Flexural and shear behaviors of reinforced UHP-ECC beams show superior performance than RC beams.•Feasibility of utilizing UHP-ECC to largely reduce steel bar in structural member was proved. The structural behaviors of steel reinforced ultra-high performance engineered cementitious composites (UHP-ECC) beams under bending were experimentally explored and compared to the ordinary reinforced concrete (RC) beams in present research. Two series of beams, reinforced or unreinforced with stirrups, were prepared to study the flexural and shear performance of steel reinforced UHP-ECC (RU) beams. The UHP-ECC was featured with the tensile strength of 16 MPa and the tensile strain capacity around 8%. The steel reinforcement ratios of longitudinal bar for both RU and RC beams were 0.69%, 1.86% and 2.94%, respectively. The crack propagation and the failure mode of RU and RC beams were monitored by digital image correlation (DIC) method. Additionally, the load-displacement relationships, the ductility index values and the component strains including steel bar and UHP-ECC of RU beams were obtained and compared with RC beams. It was found that the RU beams showed superior performance in both load capacity and ductility at the ultimate limit state; while the crack width and deflection at the serviceability limit state of RU beams were much smaller than those of RC beams. The loading capacity of non-steel reinforced UHP-ECC (NU) beams was approaching to the one of RC beams with reinforcement ratio of 1.86%, which indicated the feasibility of utilizing the UHP-ECC to substantially reduce or replace the steel bar in structural members.